Peningkatan Efektivitas Promosi Klinik NU Beauty melalui Pengembangan Media Digital - Esih Nurasiah Jamil; Yulianingsih Yulianingsih (Jurnal PKM Manajemen Bisnis, 2026)
This Community Service Program (PkM) was initiated in response to the limited effectiveness of promotional strategies used by NU Beauty Clinic in Jonggol, Bogor, which struggled to reach a wider audience due to minimally informative messages and restricted use of digital media. The program, conducted in October 2025 by lecturers and students of Universitas Djuanda and attended by 15 clinic employees, aimed to strengthen the clinic’s marketing communication through digital-based promotional improvements. Using interviews, observations, discussions, problem analysis, and the implementation of digital solutions, the team identified that previous promotional content relied heavily on before–after photos without explaining service benefits, treatment types, or customer testimonials, while promotional channels were limited to WhatsApp and Instagram. The PkM activities resulted in enhanced promotional content and the development of additional digital platforms such as TikTok and Facebook, enabling the clinic to expand audience reach and improve visibility. These efforts provided more relevant communication alternatives for the clinic’s target market and contributed to a more structured and sustainable promotional strategy. Overall, the program is expected to support NU Beauty Clinic in strengthening its competitiveness and increasing business revenue through effective and comprehensive digital marketing practices.